Adverse effect of Abuse During Childhood on Criminal Behavior and Type of Crime among Prisoners at Forensic Mental Health Department - Ali, Hadeel S.; Mohammed, Saja H. (South Eastern European Journal of Public Health, 2024)
A quantitative approach using a descriptive-analysis design was used in the present study to find out the impact of child abuse on criminal behavior among prisoners in the forensic department. The period of the study was from 16th of October 2023 to 10th of June 2024. The study has been conducted at Al-Rashad Training Hospital which is located in of Baghdad City. Non-probability sampling techniques in which prisoners are selected because they have characteristics that we need in our sample. In other words, prisoners are selected “on purpose” as purposive sampling. Also the judgmental sampling, this sampling method relies on our judgment when identifying and selecting the prisoners that can provide the best information to achieve the study’s objectives. We choose purposive sampling because the researcher wants to focus in-depth on relatively small samples. A purposive sample of (110) prisoners was selected from Al-Rashad Training Hospital. The study sample in this research was selected from prisoners in the forensic department in the hospital. Results: Prisoners have moderate to high level of psychological abuse during childhood. They have moderate to high level of physical abuse during childhood. prisoners having moderate to high level of sexual abuse during childhood. Also they have moderate to high level of neglect during childhood. As overall prisoners have high level of abuse during childhood. prisoners having moderate to high level of criminal behavior subdomain (socialization). related to criminal behavior subdomain (Social conditions) among prisoners; the findings indicates that prisoners having moderate to high level of criminal behavior subdomain (Social conditions) among items. The findings indicates that prisoners having moderate to high level of criminal behavior subdomain (Personal and psychological circumstances) among items. Prisoners have high level of criminal behavior as overall. There is high significant relationship between Abuse during childhood and Criminal behavior at p-value= .004. There are significant relationships between (psychological, physical, sexual abuse) during childhood and criminal behavior at p-value= 0.05. There are no significant relationships between neglect during childhood and criminal behavior. There is no significant relationship between Abuse during childhood and type of crime at p-value= .05.